Asian values - Vittachi, Nury ([Hong Kong] : O'Donald Publications Ltd., 1996)
Nury Vittachi is a journalist and author based in Hong Kong. His columns are published daily, weekly in a variety of newspapers in Asia as well as on his website. He is best known for the comedy-crime novel series The Feng Shui Detective, published in many languages around the world, but he has also written non-fiction works and novels for children. He is also noted for his role in founding the Asia Literary Review, the Hong Kong International Literary Festival, the Man Asian Literary Prize, and was the chairman of the judges of the inaugural Australia-Asia Literary Award in 2008. Vittachi currently lives in Hong Kong with his English wife Mary-Lacey Vittachi and their three adopted Chinese children.
Asian values /, Asian
Keywords: ASIA -- VALUES